Comparison of efficacy and toxicity between botulinum toxin subtypes A1 and A2 in cynomolgus macaques. (October 2018) - Torii, Yasushi; Sasaki, Mikio; Shin, Min-Chul; Akaike, Norio; Kaji, Ryuji
Abstract: Botulinum toxin type A (subtype A1) is used as therapeutic agent for some neurological disorders causing spasticity. The toxin products have an upper dosage limit, and their adverse events, such as side effects of diffusion following high-dose administration, have become serious issues. Therefore, a preparation with greater therapeutic efficacy at lower dosages and less diffusion in the body is desired. We have attempted to produce neurotoxin derived from subtype A2 (A2NTX), which has a different amino acid sequence from that of neurotoxin derived from subtype A1. In this study, to investigate whether A2NTX is applicable for treatment, we compared the muscle relaxation effects and the toxicity between A1LL and A2NTX in adult cynomolgus macaques. In the isometric muscle contraction test elicited by 30 Hz tetanus stimulation, the contractions observed in the 0.4 U/site A1LL-treated group were similar in value to those in the 0.13 U/site A2NTX-treated group. In the toxicity test, the 12 and 24 U/kg A1LL- and A2NTX-treated groups all exhibited similar signs of toxicity regarding symptoms, rate of weight loss, and decrease in the length of the right lower leg perimeter. Thus, A2NTX demonstrated approximately 3.0-times higher muscle relaxation activity than A1LL, and their toxicity was equivalent. This study suggested that A2NTX products are more suitable for the treatment of neurological disorders. Highlights: We compared the muscle relaxation effects and the toxicity between A1LL and A2NTX in the adult cynomolgus macaques. In the efficacy test, the relative potency of A2NTX was approximately 3.0 times than that of A1LL as 1.0. The toxicity of A1LL and A2NTX was equal. Our results suggested that A2NTX products may be more suitable for the treatment of neurological disorders.